Anti-HIV1 and anti-inflammatory lupanes from the leaves, twigs, and resin of garcinia hanburyi - Vichai Reutrakul (2018)
Two new lupanes, 2-acetoxy-3-hydroxy-19-hydrogen-lup-20(29)-en-28-oic acid (2-acetoxyalphitolic acid) (1) and 2-hydroxy-3-acetoxy-19-hydrogen-lup-20(29)- en-28-oic acid (3-acetoxyalphitolic acid) (2), together with the known betulinic acid (3), betulin (4), and stimasterol-3-O - D-glucopyranoside (5), were isolated from the leaves and twigs of Garcinia hanburyi. Compounds 13 were also isolated from the resin of this plant. The structure of 2 was confirmed by single-crystal X-ray diffraction analysis. All of the lupanes (14) displayed anti-HIV1 activities in the anti-HIV1 reverse transcriptase (ICvalues 16.3116.9g/mL) and syncytium assays (EC5.673.6g/mL, SI 1.73.3). Moreover compounds 14 exhibited anti-inflammatory activity in an ethyl phenylpropiolate (EPP)-induced ear edema model. © Georg Thieme Verlag KG Stuttgart New York.